Bone marrow edema-like lesions (BMELs) are associated with higher T1ρ and T2 values of cartilage in anterior cruciate ligament (ACL)-reconstructed knees: a longitudinal study - Gong, Jingshan; Pedoia, Valentina; Facchetti, Luca; Link, Thomas M.; Li, Xiaojuan (Quantitative Imaging in Medicine and Surgery, 2016)
Background: To evaluate the longitudinal changes of bone marrow edema-like lesions (BMELs) in patients after anterior cruciate ligament (ACL) reconstruction and to investigate the effect of BMELs on cartilage matrix composition changes measured using MR T1ρ and T2 mapping. Methods: Patients with acute ACL tear were enrolled in a prospective study. MR imaging was performed at baseline (before surgeries) and at 6-month, 1-year and 2-year after ACL reconstruction. MR imaging included sagittal high-resolution, 3D fast spin-echo (CUBE) sequences for BMEL evaluation, and 3D T1ρ mapping and T2 mapping for cartilage assessment. BMELs were assessed using whole-organ magnetic resonance imaging score (WORMS), and the volume of BMELs was measured by a semi-automatic method. Generalized estimating equation (GEE) was used to explore association between BMELs at baseline and cartilage changes during follow-up. Results: Fifty four patients were included in the present study and 39 patients had completed 2-year follow-up. BMELs were noted in 42 injured knees (77.8%) with 105 lesions and in 7 contralateral knees (13.0%) with 9 lesions (χ2=45.763, P